Pengaruh Budaya Organisasi terhadap Kompetensi Guru untuk Mewujudkan Kinerja Guru (Penelitian di SD Garut Islamic School Prima Insani) - Wahyuni, Sri; Masripah; Anisa Larasati, Retno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of organizational culture on teacher competence and its implications for realizing teacher performance at Garut Islamic School Prima Insani. The research employed a quantitative approach using descriptive-analytical methods and path analysis. The population consisted of 52 teachers selected using a saturated sampling technique. Data were collected through questionnaires, observations, and documentation. The findings demonstrate that organizational culture significantly influences teacher competence by 61.4%, teacher competence significantly influences teacher performance by 76.9%, and organizational culture significantly influences teacher performance by 72.9%. These results highlight the importance of strengthening organizational culture and enhancing teacher competence to improve teacher performance.